Misalignment of Lung Vessels and Alveolar Capillary Dysplasia: A Case Report With Autopsy - Shih-Pin Hung; Shih-Hung Huang; Chun-Hung Wu; Wu-Charng Chen; Ka-Em Kou; Nan-Koong Wang; Lung-Huang Lin (Elsevier, 2011)
Misalignment of lung vessels (MLV) with or without alveolar capillary dysplasia (ACD) is a rare cause of idiopathic persistent pulmonary hypertension of the neonate. This report describes a full-term infant with severe and intractable pulmonary hypertension. The patient's condition progressively deteriorated despite high-frequency oscillatory ventilation, infusion of magnesium sulfate, dopamine, and dobutamine to control blood pressure, and nitric oxide inhalation therapy. The infant died at 5 days of age. The diagnosis of MLV with ACD was established by autopsy. Histopathologic analysis revealed a failure of formation and an ingrowth of alveolar capillaries, thickening of the alveolar walls, poor contact of capillaries with alveolar epithelium, small intra-acinar muscularized arterioles, and anomalous pulmonary veins within bronchovascular bundles. The low rate of diagnosis of MLV with or without ACD may be because of the early high mortality rate or patchy involvement in some cases. Increasing awareness of this clinical entity may prevent the use of costly, invasive, and probably ineffective procedures. Short-term improvement after inhalation of nitric oxide does not lead to long-term survival but merely provides time for potential lung transplantation.